2014
DOI: 10.1111/cei.12432
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 stimulation promotes Ro52/TRIM21 synthesis and nuclear redistribution in salivary gland epithelial cells, partially via type I interferon pathway

Abstract: SummaryUp-regulated expression of Ro52/tripartite motif-containing protein 21 (TRIM21), Ro60/TROVE domain family, member 2 (TROVE2) and lupus LA protein/Sjögren's syndrome antigen B (La/SSB) autoantigens has been described in the salivary gland epithelial cells (SGEC) of patients with Sjögren's syndrome (SS). SGECs, the key regulators of autoimmune SS responses, express high levels of surface functional Toll-like receptor (TLR)-3, whereas Ro52/TRIM21 negatively regulates TLR-3-mediated inflammation. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 46 publications
4
54
0
2
Order By: Relevance
“…28 In addition, expression and location of Ro52 in different cellular compartments have been modulated by activation of innate immunity through toll-like receptor 3 (TLR3), interferon-alpha (IFN-α) and nitric oxide. [29][30][31] In NZM2758 mice, we observed that alum treatment caused significant upregulation of circulating KC, IL-1α, MIG, MIP2 and PDGF-β (see online supplementary figure S5). At present it is unclear as to how these cytokines influence antibody-mediated SG dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…28 In addition, expression and location of Ro52 in different cellular compartments have been modulated by activation of innate immunity through toll-like receptor 3 (TLR3), interferon-alpha (IFN-α) and nitric oxide. [29][30][31] In NZM2758 mice, we observed that alum treatment caused significant upregulation of circulating KC, IL-1α, MIG, MIP2 and PDGF-β (see online supplementary figure S5). At present it is unclear as to how these cytokines influence antibody-mediated SG dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…GF animals are free of viruses except endogenous retroviruses, which have been shown to stimulate MyD88 pathway through toll-like receptor (TLR)-7 (34). In SPF mice other viruses may contribute to sialitis even in MyD88-independent manner: stimulation of MyD88-independent TLR3, which is highly expressed on the surface of salivary gland epithelial cells from Sjögren patients (35), by viral dsRNA is considered a likely contributor to Sjögren’s syndrome (36). …”
Section: Resultsmentioning
confidence: 99%
“…Further studies using human salivary epithelium support a role for TLR3 ligation in glandular apoptosis [84, 96]. Importantly, activation of TLR3 expressed by SGECs induces secretion of BAFF and promotes the synthesis of Ro52, an autoantigen included in the diagnostic criteria for SS [9799]. Data from mouse models and SS patients show that both local and systemic BAFF expression is integral to SS pathogenesis.…”
Section: Mechanisms Of Innate Immune Activation In Ssmentioning
confidence: 99%